Yield Gap in Agriculture- Evidence from a Northern District of West Bengal, India - Das, K. K. (International Journal of Bio-resource and Stress Management, 2023)
Crop yield is one of the important parameters in judging the farm efficiency. The ‘gap’ in between the potential frontier of crop yield and the ‘achievement’ thereof indicates about inefficiency in farming which is thought to be a prime reason for agricultural backwardness in northern part of West Bengal, an important agrarian state in India. The study was undertaken in Coochbehar, a purposively selected West Bengal district, with the objective of exploring the ‘magnitude’ of yield gap in major crops. The study is based on both primary and secondary data. Time series analysis identifies positive but relatively ‘sluggish’ pace of growth for yield of major crops in the district. Yield gap was identified separately for smaller (Net cropped area <1.0 ha) and larger (Net cropped area >1.0 ha) farmers for prevailing major crops like winter paddy, potato, maize, jute and summer paddy etc. Yawning gaps of 1.9 t ha-1 in winter paddy, 3.24 t ha-1 in summer paddy, 0.54 t ha-1 in jute etc. do exist in between the experimental yield and the farmers’ average yield. The resultant economic loss is also of greater magnitude. Yield gap is relatively more prominent for smaller farmers. Standard of farm family education, degree of extension contact, manures and fertilizer (especially N) application has tremendous positive impact on yield improvement and subsequent reduction in ‘yield gap’. Regular awareness campaign and training on crop practices alongwith with institutional support are thought to be urgently necessary for improving the ‘lagged’ situation.